Unraveling Natalizumab Effects on Deregulated miR-17 Expression in CD4+ T Cells of Patients with Relapsing-Remitting Multiple Sclerosis. (12th May 2014) - Meira, Maria; Sievers, Claudia; Hoffmann, Francine; Rasenack, Maria; Kuhle, Jens; Derfuss, Tobias; Kappos, Ludwig; Lindberg, Raija L. P.
Abstract : MicroRNAs (miRNAs) are a family of noncoding RNAs that play critical roles in the posttranscriptional regulation of gene expression. Accumulating evidence supports their involvement in the pathogenesis of multiple sclerosis (MS). Here, we compare miR-17 expressions in CD4 + T cells from relapsing-remitting (RR) MS patients treated with natalizumab versus untreated patients. miR-17 was downregulated under natalizumab treatment and upregulated during relapse, therefore supporting a possible role of miR-17 in MS immunopathogenesis. Downregulation of miR-17 was associated with upregulation of PTEN, BIM, E2F1, and p21 target genes. In vitro miR-17 inhibition was associated with upregulation of the same targets and resulted in impaired CD4 + T cell activation and proliferation. We further describe deregulated TGFBR2 expression in untreated patients versus healthy volunteers (HVs) and confirm in vitro the link between miR-17 and TGFBR2 expressions. These findings support an effect of natalizumab on expression of specific miRNA and subsequent expression of genes involved in proliferation and control of the cell cycle.